Sintesa Zeolit 4A Dari Kaolin Menggunakan Proses Peleburan Dengan Variasi Perbandingan Volume Reaktan - Putra, Ryan Prakarsa; Akbar, Fajril; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Zeolite 4A can be used as phosphate replacement for detergents synthesis. It can be synthesized from calcined kaolinite . The results of the kaolin analysis indicated that composition of silica in kaolin larger than alumina, there for in the process of zeolite 4A synthesis need additional of alumina compound. In this research examine the possibility of kaolin as the source of silica in zeolite 4A synthesis with variations in the volume of reactants ( 20:80 , 40:60 , 50:50 , 60:40 , 80:20 ). The reactant compound was synthesis by reaction of sodium silicate (kaolin remelting with sodium hydroxide) and sodium aluminate . Zeolite 4A was synthesis by stirring up the sodium silicate with sodium aluminate for 2 hours until white gel formed. Then synthesized at 80Â â°C temperature for 8 hours. The result of the synthesis filtered and washed with distilled water until neutral pH, and then dried in oven at 120â° C temperature for 3 hours. The forming of zeolite characterized by infrared spectrophotometry and X-ray diffractometer. Maximal zeolite 4A synthesized was form the variation of sodium silicate and sodium aluminate ratio at 60:40 with 1.53 ratio. The comparison of diffractogram concluded that zeolit synthesis in this study was zeolite 4A.. Â Keywords : Infrared Spectroscopy , Kaolin ,X-Ray Diffraction , Zeolite 4A